Three houses : Glenn Murcutt - Farrelly, E. M. (Architecture in detail (London, England), 2002)
Murcutt's houses bring together the minimalist Miesian pavilion with the primitive hut to produce a new, striking and peculiarly Australian synthesis. The three houses covered in this volume chart the development of his unique style. The Marie Short House, with its shed-like appearance, inaugurated the architect's primitive treatment of form. Despite its tough exterior, the timber-lined interior of the building is a masterpiece of delicacy and warmth. The Ball-Eastaway House, designed for two artists as a dual gallery and dwelling-place, takes the primitive aesthetic further and is constructed entirely from corrugated iron. The definition of the interior spaces in this building invited comparison with Mies van der Rohe's famous Barcelona Pavilion. Magney House with its expressive wave-shaped metal roof marks a new level of confidence and maturity. All three houses demonstrate an alliance between refinement and primitiveness that is characteristic of Glen Murcutt's work.